A evolução dos gastos e a eficiência das políticas públicas de educação e saúde da microrregião de Paranaguá, PR - Bonatto, Hamilton (2020)
When society assigns the public budget execution to the political agent, it expects a result consistent with its needs, especially when it comes to primordial social areas such as education and health. That brings up the importance of evaluating how these expenses occur and how they return to the people. With this idea as a starting point, this work intends to evaluate the evolution of public spending and quality indicators, as well as to verify the relationship between these public spending and the efficiency in public policies in the areas of education and health in the municipalities of the microregion of Paranaguá, PR. For this, the bibliographic review and the verification of official data related to the financial aspects of the municipalities of the microregion under study were used as methodology só that, with the scope of limiting a frontier of efficiency of the public expenses, instrumentalized by the Data Envelopment Analysis – DEA (Data Envelopment Analysis), the micro-region benchmarking municipalities could be revealed and serve as basis for the improvement of other municipalities in public education and health policies. Efficiency was measured by comparing the outcome of public policies in these areas of each municipality with the best result observed among all municipalities analyzed in the execution of these policies. To analyze the efficiency in public education, the GDP per capita and the expenditure per capita in this area were used as input; The output used was the Education Development Index and the Approval Rate, both related to elementary education. For public health analysis, the GDP per capita and expenditure per capita in this area were chosen as input; The output adopted was the Ipardes Index of the area and the Infant Mortality Rate. Both analyzes were performed by the classic methods of Constant Return to Scale – CRS and Variable Returns to Scale – VRS, both oriented by the outputs, from 2008 to 2016, every four years. As a result, it was observed that the indexes that assess the quality of public education and health functions are directly proportional to the investment in these municipal public policies. Regarding the evaluation of the efficiency of these functions in the municipalities of the microregion under study, it is observed that both by the CRS method and the VRS method, there is a consistency in the results. In education, the most efficient municipality was Matinhos, in the three periods, 2008, 2012 and 2016; in the public health function, the municipality of Morretes was the most efficient in 2008 and 2016, while in 2012 it was the municipality of Pontal do Paraná.